2016
DOI: 10.1080/09273948.2016.1213855
|View full text |Cite
|
Sign up to set email alerts
|

Cataract Surgery with Primary Lens Implantation in Children with Chronic Uveitis

Abstract: Cataract surgery with primary posterior chamber hydrophobic IOL implantation is possible and leads to a good visual recovery in cases of pediatric chronic uveitis. This surgery requires aggressive anti-inflammatory management with immunosuppressive drugs to control inflammation and reduce the corticosteroids dosage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…Taken together, studies found that cataract surgery, regardless of IOL implantation, generally improved vision. Nearly all studies specifically highlighted the need for intensive immunosuppressive treatment and control of uveitis after cataract surgery, but it was unclear whether it was a question of sustaining preexisting regimen or based on a change in the need for controlling the uveitis [16,20,21,[32][33][34][35][36].…”
Section: Results Of Individual Studies and Risk Of Bias Within Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Taken together, studies found that cataract surgery, regardless of IOL implantation, generally improved vision. Nearly all studies specifically highlighted the need for intensive immunosuppressive treatment and control of uveitis after cataract surgery, but it was unclear whether it was a question of sustaining preexisting regimen or based on a change in the need for controlling the uveitis [16,20,21,[32][33][34][35][36].…”
Section: Results Of Individual Studies and Risk Of Bias Within Studiesmentioning
confidence: 99%
“…Risk of bias assessment was challenged in three studies since we only had access to conference abstracts with limited information [30][31][32]. Remaining studies had moderate-toserious risk of bias (Table 4), in which the key source of bias was the baseline confounding from the fact that the allocation to either IOL implantation or aphakia across studies was based on the individual surgeon's estimation of whether or not pseudophakia or aphakia would benefit the patient best.…”
Section: Results Of Individual Studies and Risk Of Bias Within Studiesmentioning
confidence: 99%
See 3 more Smart Citations